Ocean component of the first operational version of Hurricane Analysis and Forecast System: Evaluation of HYbrid Coordinate Ocean Model and hurricane feedback forecasts - Kim, Hyun-Sook; Liu, Bin; Thomas, Biju; Rosen, Daniel; Wang, Weiguo; Hazelton, Andrew; Zhang, Zhan; Zhang, Xueijin; Mehra, Avichal (Frontiers in Earth Science, 2024)
The first operational version of the coupled Hurricane Analysis and Forecast System (HAFSv1), accepted in 2023, consists of the HYbrid Coordinate Ocean Model (HYCOM) and Finite-Volume Cubed-Sphere dynamic atmosphere model. The system is a product of efforts by improving and updating the system for the four year period (2019)(2020)(2021)(2022), through extensive collaboration between the Environmental Modeling Center at the US National Centers for Environmental Prediction and the NOAA Atlantic Oceanography and Meteorology Laboratory. In this paper, we evaluate HYCOM performance with two official configurations, HFSA and HFSB, with the objective to document the ocean forecast skill in the dynamically coupled systems. We chose Hurricane Laura (2020) as an exemplary case that demonstrates interactions between the storm and oceanic mesoscale features. Comparisons performed with available in-situ observations from gliders, Argos and National Data Buoy Center moorings show that HYCOM's simulations agree better for weak winds than for high winds (greater than Category 2). Skill metrics indicate that model sea surface temperature (SST) and mixed layer depth (MLD) have relatively low correlation. SST, MLD, mixed layer temperature (MLT) and Ocean Heat Content (OHC) are negatively biased. For high winds, SST and MLT become further negative, while MLD becomes closer to the observations by about 8 -19% improvement. The OHC discrepancy is proportional to predicted wind intensity. To the contrary, mixed layer salinity (MLS) uncertainties are smaller positive for higher winds, probably due to deepening MLD. The less negative bias of MLD for high winds implies that the wind-force mixing is less effective, owing to deepened MLD and high buoyancy stability (~1.5 -1.7 times) than the observation. The heat budget analysis suggested that the maximum heat loss by Laura was O(< 3 o C per day). The main contributor is the advection, followed by the entrainment; and they act against or with each other, depending on the storm quadrant. We also found relatively large unaccountable heat residuals for the in-storm period, and the residuals notably led the heat tendency, which means that further improvement of subscale simulations is warranted. In summary, HYCOM simulations showed no systematic differences forced by either HFSA or HFSB.